Hospitality as a Ritual Liminal-Stage Relationship with Transformative Power: Social Dynamics of Hospitality and Patronage in the Third Epistle of John. (August 2019) - Lorencin, Igor
Hospitality is a ritual liminal-stage relationship with transformative power. In this article, I am testing my thesis about hospitality within the third epistle of John. In writing recommendation for strangers, the elder of 3 John sought to speed up the ritual liminal stage of hospitality so as to make strangers acceptable to the local church. Gaius was ready to give the strangers a chance and to enter the liminal stage for the purpose of transforming them into a new status as his household's friends. On the other hand, Diotrephes practiced patronage, which included no liminality and no expectation of passage or transformation of social roles, but rather kept the social status quo and protected his area of influence. It follows from this analysis that hospitality with its liminality contributes to social change and renewal, while patronage contributes to social stability and continuation.